2010
DOI: 10.1373/clinchem.2009.136283
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Aspirate Fluid Proteome of Healthy Females and Patients with Breast Cancer

Abstract: BACKGROUND:The ductal/alveolar system of the female breast constantly secretes and reabsorbs fluid in nonpregnant/nonlactating women. This fluid, referred to as nipple aspirate fluid (NAF), can be obtained by a noninvasive procedure and it is part of the microenvironment where more than 95% of breast cancers arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
(16 reference statements)
1
33
0
Order By: Relevance
“…Venn diagrams illustrating (C). overlapping identities with the data from the NAF study by Pavlou et al 20, and D. overlapping identities with the Human Plasma Proteome database.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Venn diagrams illustrating (C). overlapping identities with the data from the NAF study by Pavlou et al 20, and D. overlapping identities with the Human Plasma Proteome database.…”
Section: Resultsmentioning
confidence: 90%
“…Prior to this study, the most complete proteomics profile of NAF was that of Pavlou et al. 20. Comparison with our dataset, based on gene identity (691 entries Pavlou et al., and 1919 for our set, excluding immunoglobulin isoforms), indicated an overlap of 563 proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, targeted multiplex mass spectrometry is emerging as a novel quantitative strategy for measuring protein signatures in tumor tissues or blood. Proteomic studies of breast cancer cells and tissues have already shown the potential for candidate biomarkers discovery (17)(18)(19)(20)(21)(22). In a promising pilot study using SELDI-TOF-MS, serum peptide profiles could distinguish women with BRCA1 mutations who developed breast cancer from those who did not (carrier), normal volunteers, and women with sporadic breast cancer with good sensitivity and specificity (23).…”
mentioning
confidence: 99%
“…However, this certainly does not preclude using NAF as a source for protein biomarker discovery efforts. A recent study employed multifractionation strategies prior to peptide analysis on an LTQ Orbitrap mass spectrometer and reported over 800 unique proteins present in NAF (Pavlou et al, 2010). Approximately 40% of these proteins are also found in serum/plasma, and over 50% of them were secreted or of plasma membrane origin.…”
Section: Detection Of Breast Cancer Biomarkers In Nipple Aspirate/ducmentioning
confidence: 99%